Sistem Monitoring Tanaman Hidroponik Berbasis Internet of Things menggunakan Restful API - Rivaldo, Karel Leo; mogi, I Komang ari; Suputra, I Putu Gede Hendra; Sanjaya, Ngurah Agus; Darmawan, Dewa Made Bayu Atmaja; Dwidasmara, Ida Bagus Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 1 (2022): JELIKU Volume 11 No 1, August 2022DO - 10.24843/JLK.2022.v11.i01.p11, 2022)
Agricultural technology is one of the important things in today's era. one of the Indonesian government programs made is a roadmap with the name Making Indonesia 4.0. in the agricultural roadmap program one of the important technology applications is hydroponic agriculture, in the implementation of hydroponic plants a good form of data communication is needed, therefore in this study the author uses a form of data communication with Restful Architecture API as communication in the hydroponic agriculture monitoring system. In this study, two tests were carried out, namely the test was carried out by testing the system in sending sensor data and the second. System testing in reading and controlling the pH sensor value with parameter intervals of 1 second, 5 seconds, 10 seconds, 20 seconds, and 30 seconds. The results obtained in this study are 30 seconds is the best time in the process of sending data one interval from the microcontroller to the system.